Orthobunyaviruses: from virus binding to penetration into mammalian host cells - Windhaber, Stefan; Xin, Qilin; Lozach, Pierre-Yves (Viruses, 2021)
With over 80 members worldwide, Orthobunyavirus is the largest genus in the Peribunyaviridae family. Orthobunyaviruses (OBVs) are arthropod-borne viruses that are structurally simple, with a trisegmented, negative-sense RNA genome and only four structural proteins. OBVs are potential agents of emerging and re-emerging diseases and overall represent a global threat to both public and veterinary health. The focus of this review is on the very first steps of OBV infection in mammalian hosts, from virus binding to penetration and release of the viral genome into the cytosol. Here, we address the most current knowledge and advances regarding OBV receptors, endocytosis, and fusion.